Vertical Mastectomy Incision in Implant Breast Reconstruction After Skin Sparing Mastectomy: Advantages and Outcomes. (June 2016) - Dayicioglu, Deniz; Tugertimur, Bugra; Zemina, Kristen; Dallarosa, Johnathan; Killebrew, Sequoya; Wilson, Augustine; Atisha, Dunya; Khakpour, Nazanin
Abstract : Background: The type of since skin-sparing mastectomy (SSM) incision directly impacts the final aesthetic and functional results of reconstruction. Different incisions are used for SSM depending on tumor location, previous biopsy scars, breast weight, and ptosis degree. A vertical scar is less visible to the patient, reminiscent of a mastopexy, and patients may not have the stigma of mastectomy. Objective: This study investigates complication rates, patient demographics, patient reported outcomes, and plastic surgeon evaluations to compare vertical incision mastectomy to other incisions. Methods: After institutional review board approval, a retrospective chart review was performed. A total population of 167 patients that underwent mastectomy with tissue expander reconstruction was separated into vertical incision and nonvertical incision mastectomy groups consisting of 38 and 129 patients, respectively. Patient demographics, complications, tumor margins, staging, breast weight, and breast implant volume were compared. BREASTQ Survey analysis was conducted using patient reported outcomes from the patient's perspective. Aesthetic evaluations of postoperative photos were systematically scored by plastic surgeons to obtain data from the plastic surgeon's perspective. Results: Vertical incision orientation did not increase surgical complication rates or mastectomy skin necrosis ( P = 0.142). Vertical incisions did not interfere with obtaining adequate tumor margins ( P = 0.907). Vertical incisions did not have a significantly different breast weight or implant volume. There was no statistical difference for patient satisfaction or plastic surgeon aesthetic evaluation. Conclusions: The use of vertical incision does not increase complication rates; does not interfere with tumor margins; and can be applied to all age, BMI, breast weight, and breast implant volume groups.